Molecular features of non‐anaplastic peripheral T‐cell lymphoma in children and adolescents. Issue 11 (13th August 2021) - Au‐Yeung, Rex K. H.; Richter, Julia; Iaccarino, Ingram; Abramov, Dmitriy; Bacon, Chris M.; Balagué, Olga; d'Amore, Emanuele S. G.; Simonitsch‐Klupp, Ingrid; Hebeda, Konnie; Nakazawa, Atsuko; Oschlies, Ilske; Kontny, Udo; et al.
Abstract: Non‐anaplasticperipheral T‐cell lymphomas (PTCL) are rare tumors in children, adolescents, and young adults (CAYA) with poor prognosis and scarce genetic data. We analyzed lymphoma tissue from 36 patients up to 18 years old with PTCL, not otherwise specified (PTCL‐NOS), hepatosplenic T‐cell lymphoma, Epstein–Barr virus (EBV)‐positive T‐lymphoproliferative diseases, subcutaneous panniculitis‐like T‐cell lymphoma, and other PTCL types. Twenty‐three patients (64%) had at least one genetic variant detectable, including TET2, KMT2C, PIK3D, and DMNT3A . TP53 and RHOA variants, commonly found in adults, were not identified. Eight of 20 (40%) CAYA PTCL‐NOS had no detectable mutations. The genetic findings suggest that CAYA PTCL differ from adult cases.